Association of Albuminuria With 1‐Year Risk of Heart Failure and Other Adverse Outcomes in Atrial Fibrillation - Odutayo, Ayodele; Serrano, Alicia; Chauhan, Anjali; Fang, Jiming; Sud, Maneesh; Han, Lu; Austin, Peter C.; Dorian, Paul; Jackevicius, Cynthia A.; Lee, Douglas S.; Singh, Sheldon M.; Tu, Karen; et al. (Journal of the American Heart Association, 2025)
Albuminuria is associated with increased stroke risk in atrial fibrillation (AF), but its relationship with heart failure (HF) and other adverse outcomes in AF is less well understood. Using linked administrative databases, we conducted a retrospective cohort study of individuals aged ≥66 years who were newly diagnosed with AF between April 2009 and March 2019 in Ontario, Canada. Albuminuria was assessed using (1) urine albumin-to-creatinine ratio (UACR, mg/g) and (2) dipstick proteinuria (negative, trace, 1+, 2+, ≥3+). Cause-specific hazards regression estimated adjusted hazard ratios (HRs) for HF hospitalizations or emergency department visits, stroke hospitalizations, bleeding hospitalizations, and death over 1 year. We included 64 717 individuals with UACR data and 110 430 with dipstick proteinuria data. Relative to UACR 5 mg/g, the HRs for UACR 30 mg/g (below the microalbuminuria threshold) were 1.39 (95% CI, 1.28-1.50) for HF, 1.22 (95% CI, 1.07-1.40) for bleeding, and 1.35 (95% CI, 1.27-1.42) for death. A UACR of 30 mg/g versus 5 mg/g was associated with an HR of 1.16 (95% CI, 0.99-1.36) for stroke but the HR was significantly elevated at UACR values ≥65 mg/g. Increasing dipstick proteinuria was also associated with increases in the HR for adverse outcomes. A UACR of 30 mg/g was associated with greater HF risk (versus 5 mg/g) than all CHA₂DS₂VASc components except age >75 years and prior HF. Albuminuria is associated with increased hazards of HF, stroke, bleeding, and death in patients with AF even at low UACR levels. Albuminuria may enhance risk stratification in AF beyond traditional scores.